(untitled) (Third Sector Social Economic Review, 2014)
While mobilizing local potential in performance of activities, developmental agencies need to put forward a plan to make effective and efficient use of regional resources as well. Since these institutions are characterized by different structure and legal status in the world, the homogeneity in their methods to control and implementations is eliminating. This heterogeneity of standards and methods brings ambiguity in administrative control. Likewise, Turkey is also experiencing the same situation. Agencies in Turkish Public Administration System, belong to either public or private corporations, are ambiguous from point of view of legal and organizational control. Despite agencies are having public law (article. 5449) for the improvements of organizational activities, revenues, status of public officials and similar other aspects, controlling dilemma is prevailing because of following private law in this regard. Even appointed governors of the agencies usually go against the autonomy of the organizations, and likewise they do the same on legal grounds, governance, and subsidiary principles. The aim of this study is to examine and discuss administrative control system of developmental agencies specifically from organizational and legal status perspectives; also proposes an effective administrative structure that can contribute to the regional development.